MnSOD and Cyclin B1 Coordinate a Mito-Checkpoint during Cell Cycle Response to Oxidative Stress - Amanda L. Kalen; Iman M. Ahmad; Maher Y. Abdalla; Yunxia Q. O'Malley; Prabhat C. Goswami; Ehab H. Sarsour (MDPI AG, 2017)
Communication between the nucleus and mitochondrion could coordinate many cellular processes. While the mechanisms regulating this communication are not completely understood, we hypothesize that cell cycle checkpoint proteins coordinate the cross-talk between nuclear and mitochondrial functions following oxidative stress. Human normal skin fibroblasts, representative of the G2-phase, were irradiated with 6 Gy of ionizing radiation and assayed for cyclin B1 translocation, mitochondrial function, reactive oxygen species (ROS) levels, and cytotoxicity. In un-irradiated controls, cyclin B1 was found primarily in the nucleus of G2-cells. However, following irradiation, cyclin B1 was excluded from the nucleus and translocated to the cytoplasm and mitochondria. These observations were confirmed further by performing transmission electron microscopy and cell fractionation assays. Cyclin B1 was absent in mitochondria isolated from un-irradiated G2-cells and present in irradiated G2-cells. Radiation-induced translocation of cyclin B1 from the nucleus to the mitochondrion preceded changes in the activities of mitochondrial proteins, that included decreases in the activities of aconitase and the mitochondrial antioxidant enzyme, manganese superoxide dismutase (MnSOD), and increases in complex II activity. Changes in the activities of mito-proteins were followed by an increase in dihydroethidium (DHE) oxidation (indicative of increased superoxide levels) and loss of the mitochondrial membrane potential, events that preceded the restart of the stalled cell cycle and subsequently the loss in cell viability. Comparable results were also observed in un-irradiated control cells overexpressing mitochondria-targeted cyclin B1. These results indicate that MnSOD and cyclin B1 coordinate a cross-talk between nuclear and mitochondrial functions, to regulate a mito-checkpoint during the cell cycle response to oxidative stress.